ATIM-01. A PHASE II, OPEN-LABEL, SINGLE ARM, MULTICENTER STUDY OF AVELUMAB WITH HYPOFRACTIONATED RE-IRRADIATION IN ADULT SUBJECTS WITH TRANSFORMED IDH MUTANT GLIOBLASTOMA. (6th November 2017) - Chi, Andrew S; Eisele, Sylvia; Arrillaga-Romany, Isabel; Batchelor, Tracy; Cahill, Daniel; Taylor, Jennie; Cloughesy, Timothy F; Patel, Amie; Delara, Malcolm; Latchman, Sunita; Placantonakis, Dimitris; Pacione, Donato; et al.
Abstract: INTRODUCTION: Isocitrate dehydrogenase ( IDH ) mutant gliomas are relatively indolent, however nearly all IDH mutant gliomas eventually transform to secondary glioblastoma (GBM) for which no effective salvage therapy exists. Transformation to secondary GBM is associated with a high rate of chemotherapy-induced hypermutation phenotype in IDH mutant glioma. Therefore, we aimed to test the safety and efficacy of avelumab, an anti-PD-L1 antibody, and hypofractionated re-irradiation in transformed IDH mutant GBM patients. METHODS: This is a single arm phase II trial with a 6 patient safety lead-in with the primary objectives of safety and 6-month progression-free survival (PFS6) assessment. 43 patients are planned across 4 sites. Avelumab is given 10 mg/kg intravenously every 2 weeks. RT is given in 5 consecutive daily fractions to a total dose of 25 Gy starting day 8. Major eligibility criteria include prior diagnosis of grade II or III IDH mutant glioma; progression after treatment with temozolomide; CCNU, or BCNU; receipt of prior RT; progressive tumor tissue with either histopathologic diagnosis of GBM or any glioma with evidence of mismatch repair defect, microsatellite instability, or hypermutation phenotype by next-generation sequencing; no prior PD-1/PD-L1 pathway inhibitor treatment. Secondary objectives include estimation of overall survival, PFS, and response rate. Exploratory objectives include association of PFS6 with hypermutation phenotype, proportion of predicted mutation-associated neoantigens among all somatic mutations, tumor PD-L1 expression, baseline and change in circulating regulatory T cell and myeloid-derived suppressor cell levels. RESULTS: Two patients have been enrolled in the safety lead in cohort. No DLTs were observed. Both patients experienced treatment-induced grade 2 neurological symptoms related to brain edema. Both patients are currently on study at cycle 3.  CONCLUSIONS: Avelumab and hypofractionated RT has been tolerated with no DLTs observed thus far. Enrollment in the Safety Lead-In and collection of safety and preliminary response data is ongoing.